013 Associations Between Rest-Activity Rhythms and Nocturnal Blood Pressure are Sex-Dependent in Apparently Healthy Emerging Adults. (3rd May 2021) - Hoopes, Elissa; Patterson, Freda; Berube, Felicia; D'Agata, Michele; Brewer, Benjamin; Malone, Susan; Farquhar, William; Witman, Melissa
Abstract: Introduction: Misalignment between endogenous circadian rhythms and environmental signals – an emerging risk factor for cardiovascular disease (CVD) – can disrupt diurnal blood pressure (BP) rhythms, resulting in higher nocturnal BP and less-pronounced BP dipping (i.e., % decline in nighttime systolic BP [SBP] relative to daytime values). Daily patterns of rest and activity ('rest-activity rhythms' [RAR]) are a proxy for estimating circadian disruption in free-living settings and have been independently associated with elevated CVD risk. However, the relation between RAR and nocturnal BP is unclear. Thus, we aimed to quantify the associations between RAR and nocturnal BP characteristics in male and female emerging adults (18-25y). Methods: Fifty healthy emerging adults (20±1y; 20M/30F) underwent 24-h ambulatory BP monitoring following 14 consecutive days of continuous wrist actigraphy. RAR variables of interdaily stability (IS; day-to-day consistency in RAR), intradaily variability (IV; within-day fragmentation of RAR), and relative amplitude (RA; difference between trough vs. peak activity) were computed. Bivariate correlations were used to quantify associations between RAR variables and nocturnal BP characteristics for all participants, and separately for males and females. Linear regression models of mean nocturnal SBP, nocturnal diastolic BP (DBP), and SBP dipping were also generated to test main and interactive effects of sex and RAR. Potential confounders (variables associated with outcomes at p<0.10) of daytime BP, race, body mass index, physical activity, sleep duration, alcohol, caffeine, and sodium intake were also included as indicated. Results: Overall, IS and RA positively correlated with % SBP dipping (IS: r=0.33, p=0.02; RA: r=0.35, p=0.01). Among females only, correlations strengthened (IS: r=0.50, p<0.01; RA: r=0.52, p<0.01) and an inverse association between RA and mean nocturnal SBP emerged (r=-0.46, p=0.01). Conversely, among males, no significant associations were apparent. Multivariate regressions revealed a significant sex*RAR interaction, such that in females, every 1-standard deviation increase in IS and RA were associated with an average decrease in nocturnal SBP of 5.4 mmHg (95% CI: -10.0, -0.73) and 4.8 mmHg (95% CI: -9.2, -0.34), respectively. Conclusion: Findings suggest that consistent and high-amplitude RAR associate with more favorable nocturnal BP characteristics, particularly in emerging female adults. Support (if any): Supported in part by NIH P20-GM113125.